Dukungan Perawat dalam Mengembangkan Produksi Jamu oleh Lansia - Kasran, Kasran; Arfan, Farmin (Yayasan Mandar Indonesia, 2022)
The results of the population census in Indonesia from 2010 to 2020 increased by about 7.93%. In Polewali Mandar, especially the Wonomulyo Public Health Center, in 2020 there were 3116 elderly people. The high number of elderly people in Indonesia is one of the government's jobs to actively participate in the welfare of the elderly and make the elderly as active and independent individuals. Elderly is a process of decreasing the body's resistance in the face of internal and external stimuli. To improve the welfare of life for the elderly, one of the activities that can be combined with support in earning independently by producing herbal medicine. Jamu is part of traditional medicine that has developed widely. Herbal medicine has several advantages, such as low toxicity and mild side effects. To develop and improve the quality of herbal medicine, nurse support is needed, especially one of the functions of nurses, namely providing comprehensive bio-psycho-social and spiritual services aimed at individuals, families and communities, both sick and healthy, which includes all processes of human life. In this study using a qualitative approach to see and express a situation or object in its context, this research is divided into 4 stages. The first stage is preparation, observation, data collection, and data analysis. The second stage, the nurse plans activities, selects an area, conducts observations and permits. The third stage, conducting a field survey, identifying potential elderly, carrying out product records, coordinating with nurses as facilitators to develop plans forshop creation, online the fourth stage ofrecognizing the needs of the general public (visit methods, surveys and interviews, skill needs in developing herbal medicine production for the elderly, proposals for cooperation towards the elderly and their families.